2015
DOI: 10.1158/1078-0432.ccr-14-0650
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Pathways: Targeting the Dependence of Mutant RAS Cancers on the DNA Damage Response

Abstract: Of the genes mutated in cancer, RAS remains the most elusive to target. Recent technological advances and discoveries have greatly expanded our knowledge of the biology of oncogenic Ras and its role in cancer. As such, it has become apparent that a property that intimately accompanies RAS-driven tumorigenesis is the dependence of RAS mutant cells on a number of non-oncogenic signaling pathways. These dependencies arise as a means of adaptation to Ras-driven intracellular stresses and represent unique vulnerabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 46 publications
1
45
0
3
Order By: Relevance
“…RAS signaling has been reported to directly lead to genotoxic stress stemming from generation of reactive oxygen species (ROS) and DNA hyper replication (Grabocka et al 2015). Cancer cells respond to this stress through activation of DNA damage repair (DDR) checkpoints and upregulation of the function of DDR pathways (Grabocka et al 2015).…”
Section: Kras Oncogenic Stress and Adaptationmentioning
confidence: 99%
“…RAS signaling has been reported to directly lead to genotoxic stress stemming from generation of reactive oxygen species (ROS) and DNA hyper replication (Grabocka et al 2015). Cancer cells respond to this stress through activation of DNA damage repair (DDR) checkpoints and upregulation of the function of DDR pathways (Grabocka et al 2015).…”
Section: Kras Oncogenic Stress and Adaptationmentioning
confidence: 99%
“…These data pave the way for the clinical evaluation of combinations consisting of inhibitors of MEK and SHP2 for the treatment of KRAS -driven malignancies. Lastly, oncogenic KRAS mutations have been shown to be associated with increased genotoxic stress in the affected cancer cells [67]. This observation has led to preclinical efforts aiming to target the DDR to selectively damage KRAS -mutant cells and tumors.…”
Section: Targeting Oncogenic Krasmentioning
confidence: 99%
“…This observation has led to preclinical efforts aiming to target the DDR to selectively damage KRAS -mutant cells and tumors. In particular, the cell cycle checkpoint kinase CHK1 emerged as a promising target, as it was shown that CHK1 inhibition synergized with genotoxic chemo- or radiotherapy to eradicate KRAS -mutant cancer cells [67,68,69,70]. Cell cycle checkpoint abrogation has been further explored by combined CHK1 and MAPKAP-K2 inhibition, which was recently shown to be selectively toxic in KRAS -driven cancer cells and tumors [71].…”
Section: Targeting Oncogenic Krasmentioning
confidence: 99%
“…Ras increases replication stress, causing persistent mitogenic activity, which consists of increased number of active DNA replication origins and collapsed replication forks (59). Both result in DNA damage response (DDR) (59,78). DDR is tested by DNA damage sensors and may direct the transformed cell upon 4 possible directions: proliferation, senescence, apoptosis (59) or defects in the DNA replication repair mechanisms (69).…”
Section: Why Is K-ras Mutation a Potential Alternative Initiating Evementioning
confidence: 99%
“…The last direction is quite important, as it causes inevitably genomic instability (59) (Figure 2). K-ras mutation is a major etiological factor of genomic instability (60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70)(78)(79)(80), which is absolutely necessary for the tumorigenesis process to accelerate.…”
Section: Why Is K-ras Mutation a Potential Alternative Initiating Evementioning
confidence: 99%